The Influence of Internal and External Environments on Gay Employees’ Satisfaction at Coffee Shops - Suttikun, Chompoonut; Wareebor, Sukanya (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2022)
This research aims to investigate gay employees’ motivation affecting their job satisfaction at coffee shops. Additionally, the purpose of this study is to understand employers’ characteristics and organizational environments enhancing employees’ work efficiency. The researchers employed a qualitative method using in- depth interviews with 10 (LGBT) employees who were working at a coffee shop. The participants were asked questions with three sections including (1) problems at work, (2) work motivation, (3) employer characteristics and work environment. The results show that gay employees’ satisfaction was influenced by rewards, approval from employer, work facilities, external environments, and work benefits respectively. The outcomes of this research could benefit coffee shop entrepreneurs by providing useful information regarding how to organize their business through the implementation of strategies that may lead to employee satisfaction.